2007
DOI: 10.1002/hep.21975
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated interferon alfa and ribavirin for 14 versus 24 weeks in patients with hepatitis C virus genotype 2 or 3 and rapid virological response

Abstract: , 15 and the North-C Group A recent nonrandomized pilot trial showed that hepatitis C virus (HCV) patients with genotype 2/3 and rapid virological response (RVR) had a 90% sustained virological response (SVR) rate after 14 weeks of treatment. We aimed to assess this concept in a randomized controlled trial. In the trial, 428 treatment-naïve HCV RNA-positive patients with genotype 2 or 3 were enrolled. Patients with RVR were randomized to 14 (group A) or 24 (group B) weeks of treatment. Patients were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
206
2
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(231 citation statements)
references
References 12 publications
17
206
2
6
Order By: Relevance
“…20 With a standard 24 week course of therapy, SVR rate of 80-91% has been reported in RVR achievers whereas RVR non-achievers have 36-62% SVR rate. [8][9][10][11][12]20 Similar results were noted in the present study where the SVR rates with standard 24 week therapy in RVR achievers and RVR non-achievers were 91.5% and 52.3% respectively. These data emphasize the need for extended therapy in CHC G3 patients who do not achieve RVR.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…20 With a standard 24 week course of therapy, SVR rate of 80-91% has been reported in RVR achievers whereas RVR non-achievers have 36-62% SVR rate. [8][9][10][11][12]20 Similar results were noted in the present study where the SVR rates with standard 24 week therapy in RVR achievers and RVR non-achievers were 91.5% and 52.3% respectively. These data emphasize the need for extended therapy in CHC G3 patients who do not achieve RVR.…”
Section: Discussionsupporting
confidence: 90%
“…7 However, in their study, analysis was done based on early virological response (EVR) and SVR, as the concept of rapid virological response (RVR) had not evolved by that time. After the concept of RVR evolved, it was noted that G-3 patients who do not achieve RVR have significantly lower (36-62%) SVR rates with the standard 24 week PEG-RBV therapy, [8][9][10][11][12] suggesting that extension of therapy is required in this subgroup of patients. However, the appropriate duration and the benefit of extended response guided PEG-RBV therapy for genotype 3 patients who do not achieve RVR has not been addressed adequately in literature.…”
mentioning
confidence: 99%
“…7. If no early virological response (a reduction of at least 2 log 10 in HCV-RNA in comparison with baseline) is achieved by week 12, HCV treatment should be discontinued as an SVR is unlikely (A-I) 8. Patients with genotypes 2 or 3, low viral loads (<400,000 U/mL) and mild fibrosis in whom HCV-RNA becomes undetectable in 4 weeks (a rapid virological response) may need only 24 weeks of therapy, but this can increase the relapse rate (A-III).…”
Section: Statementsmentioning
confidence: 99%
“…In a randomized study of 1311 CHC patients given only Peg-IFN + RBV, Hadziyannis et al [21] reported an SVR of approximately 80% in those infected with genotype 2 or 3 virus versus approximately 52% in those with genotype 1 virus. Several other studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] of CHC patients with genotype 2 or 3 virus, treated with either Peg-IFN or IFN, both administered with RBV, are summarized in Table 1 and show no better results with either IFN, when given in combination with RBV, for genotypes 2 and 3 viruses.…”
Section: Discussionmentioning
confidence: 99%